Modulation of Perturbed Cardiac Metabolism in Rats Under High-Altitude Hypoxia by Combination Treatment With L-carnitine and Trimetazidine - Xie, Hebing; Xu, Gang; Aa, Jiye; Gu, Shuhua; Gao, Yuqi (Frontiers in Physiology, 2021)
High-altitude hypoxia has long been recognized as a vital etiology for high-altitude illnesses. High-altitude myocardial injury (HAMI) usually occurs in people who suffered from high-altitude exposure. To date, the molecular mechanism of HAMI remains elusive, which seriously hinders the prevention and treatment of HAMI. L-carnitine and trimetazidine are classic cardiovascular protective medicines. In this study, we used the metabolomic method, based on GC/MS, to explore the changes in metabolites in rats exposed to high-altitude hypoxia and then illustrate the metabolic pathways associated with the modulatory effect of L-carnitine combined with trimetazidine on rats with high-altitude exposure. The results showed that metabolites in the myocardium in rats under high-altitude hypoxia were markedly changed, such as branched-chain amino acids (BCAA, leucine, isoleucine, and valine), taurine, succinic acid, fumaric acid, lactic acid, pyruvic acid, 3-hydroxybutyrate, and docosahexaenoic acid (DHA), while L-carnitine combined with trimetazidine modulated and improved the abnormal changes in energy substances caused by high-altitude hypoxia. L-carnitine mainly promoted the metabolism of fatty acids, while trimetazidine enhanced the glycolysis process. The combined administration of the two components not only increased the metabolism of fatty acids but also promoted aerobic glycolysis. Meanwhile, it contributed to the decrease in the elevation in some of the intermediates of the tricarboxylic acid (TCA) cycle, decrease in the production of 3-hydroxybutyric acid, and relief of the abnormal energy metabolism process in organisms and the cardiac tissue. Our analysis delineates the landscape of the metabolites in the myocardial tissue of rats that were exposed to high altitude. Moreover, L-carnitine combined with trimetazidine can relieve the HAMI through modulated and improved abnormal changes in energy substances caused by high-altitude hypoxia.